Reforming Tax and Welfare - Callan, Tim; Keeney, Mary J.; Nolan, Brian; Walsh, John R (ESRI, 2001)
This paper utilises the SWITCH model to carry out a detailed analysis of recent changes in the tax and welfare systems and to evaluate their effects in the light of policy objectives such as those set out in the National Anti-Poverty Strategy and the Programme for Prosperity and Fairness. On the basis of a detailed conceptual and empirical analysis, it sets out the considerable advantages of an approach to evaluation based on indexation rather than the conventional opening budget. International comparisons are provided and the key issues relating to the taxation of couples and individuals discussed.